Network effects in internal migration - László Lőrincz; Brigitta Németh (Hungarian Academy of Sciences, Institute of Economics, 2019)
Previous studies have shown the impact of family, community, and ethnic networks on migration. Our research focuses on the role of social networks in Hungarian internal migration. We examine the factors determining out-migration rate from municipalities, and the factors influencing location choice by analysingmigration volumes on the municipality-municipality level. We measure social network effects by the migration rate of previous years, and by the intensity of user-user connections on the iWiW online social network (representing3.7million users) between two municipalities. The migration volumes and the characteristics of the municipalities are included in the analysis based on administrative data, and the distance between municipalities are indicated by the travel time. We analyselongitudinal data for the2000-2014 period, and cross-sectional models for the year 2014. Based on multilevel and fixed-effect regression models we show that both leaving and choosing municipalities is associated with network effects: the migration of previous years, and also the connections on iWiW social network influence the current migration rate, even after controlling for each other.
Keywords: R23; 330; chain migration; internal migration; network effects; online social networks; social networks